PROSPECTS OF USING ALTERNATIVE SOFTWARE IN HIGHER EDUCATION INSTITUTIONS FOR EDUCATIONAL PURPOSES - Andreev, O. V. (Problems of Informatization and Management, 2005)
The article considers the feasibility and prospects of using free software in higher education institutions for educational purposes and provides specific recommendations in this regard. There is also a comparative description of software for Windows and Linux operating systems for different purposes.